UPAYA GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK KARAKTER DISIPLIN DALAM BERIBADAH SISWA DI SMP MUHAMMADIYAH LUBUK PAKAM - Muhammad Rifki Abdilah; Khairuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The purpose of this research is to find out the efforts, supporting factors, and inhibiting factors in shaping the discipline character in worshiping Muhammadiyah Lubuk Pakam Junior High School students. The research method used in this research is descriptive qualitative method to be able to describe the data obtained in more depth, and this type of research is field research. Data collection in this study was carried out by means of observation, interviews and documentation. The data analysis techniques used are data collection, data reduction, data presentation and conclusion drawing. The results of this study are the efforts made by Islamic religious education teachers in shaping the character of discipline in student worship, namely through teaching about the importance of prayer, by holding religious programs such as the night of fostering faith and taqwa (mabit) and dauroh al-Qur'an, then by doing habituation to students and sanctions so that students are disciplined in worship.